2016
DOI: 10.1038/srep19227
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic polyfunctionality maturation of cytomegalovirus-pp65-specific CD4 + and CD8 + T-cell responses in older adults positively correlates with response size

Abstract: Cytomegalovirus (CMV) infection is one of the most common persistent viral infections in humans worldwide and is epidemiologically associated with many adverse health consequences during aging. Previous studies yielded conflicting results regarding whether large, CMV-specific T-cell expansions maintain their function during human aging. In the current study, we examined the in vitro CMV-pp65-reactive T-cell response by comprehensively studying five effector functions (i.e., interleukin-2, tumor necrosis factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 50 publications
4
34
0
Order By: Relevance
“…The present study significantly extends recent work in a large group of (exclusively) older people with respect to UL83-specific T-cell responses [8]. That study showed a correlation between the increase of certain polyfunctional subsets (eg, exhibiting TNF, IFN-γ, and perforin expression, as well as degranulation) and the size of the UL83-specific T-cell response.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The present study significantly extends recent work in a large group of (exclusively) older people with respect to UL83-specific T-cell responses [8]. That study showed a correlation between the increase of certain polyfunctional subsets (eg, exhibiting TNF, IFN-γ, and perforin expression, as well as degranulation) and the size of the UL83-specific T-cell response.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have explored T-cell polyfunctionality at older ages, but it is not known whether this varies with respect to the CMV protein target and/or response size. Previous work on CMV-related T-cell polyfunctionality has focused on just 1 or 2 frequently recognized, reportedly dominant CMV proteins [8, 9], but it is unlikely that the polyfunctionality of 1 or 2 dominant responses sufficiently captures the overall polyfunctionality of the T-cell response (including dominant and subdominant responses) to this pathogen [10]. We therefore decided to revisit this interesting question, taking into account a wider, more representative range of CMV target proteins than previously studied.…”
mentioning
confidence: 99%
“…In addition, CMV drives both CD4+ and CD8+ T cell expansion toward terminal differentiation such as CD4+CD28null cells and CD8+CCR7 −CD45RA+ T EMRA cells. These cells are highly cytotoxic and high in granzyme and perforin expression but could simultaneously express high level of proinflammatory cytokines including IFN-γ and TNF-α (Chiu et al 2016). Production of pro-inflammatory cytokines in turn activates p38 in T cells, inhibits T cell telomerase activity, and promotes loss of CD28 and T cell differentiation, further creating a vicious cycle of immunosenescence (Macaulay et al 2013).…”
Section: And Atherosclerotic Cardiovascular Complicationsmentioning
confidence: 99%
“…A higher percentage of polyfunctional CD8 + T cells was identified in blood from young CMV‐seropositive individuals compared with CMV‐seronegative individuals. This is supported by the observation that CMV‐specific CD8 + T cells reside mainly among CCR7 − CD45RO + CD27 +/− T cells in young adults, while more clonally expanded T cells are found in the CCR7 − CD45A + CD27 − subset . There is also compelling evidence from animal models showing that CMV protects from fatal infections with other pathogenic organisms .…”
Section: Cmv‐specific Memory T‐cell Inflation Plays a Dual Role In Immentioning
confidence: 80%
“…This is supported by the observation that CMV-specific CD8 + T cells reside mainly among CCR7 À CD45RO + CD27 +/À T cells in young adults, while more clonally expanded T cells are found in the CCR7 À CD45A + CD27 À subset. 63,[74][75][76] There is also compelling evidence from animal models showing that CMV protects from fatal infections with other pathogenic organisms. 77 These preclinical studies showed that CMV may improve the function and consequently the quality of CD8 + T cells, at least in younger animals, a finding that may lend support to CMV being a critical factor in shaping 'immune fitness' to benefit younger individuals.…”
Section: Cmv-specific Memory T-cell Inflation Plays a Dual Role In Immentioning
confidence: 99%